EDUKASI UPAYA KESELAMATAN DAN KESEHATAN KERJA DI SMK NEGERI 3 KOTA JAMBI - M.Dody Izhar; Marta Butar Butar; Budi Aswin (Jurnal Salam Sehat Masyarakat (JSSM), 2020)
Work accidents and safety can occur when carrying out work in the workplace. Based on CDC data, it is known that the rate of work accidents among young workers compared to adult workers is higher for young workers. From the results of data collection obtained at SMKN 3 Jambi City who will later be young workers who understand that the understanding and implementation of K3 in students using practicum tools is in accordance with the rules so that they are at risk of having work accidents. Community service activities carried out through socialization in the form of counseling on occupational health efforts and training activities at the Occupational Health Effort Post (Pos UKK). The results of the socialization of occupational health efforts and training on Occupational Health Effort Posts showed an increase in the knowledge of students who took part in the activity when compared to before and after participating in training, from 64.00 to 74.67. Statistical results obtained p value = 0.033, meaning that there is a significant difference in the average value of the test before being given training and after being given training. The Initiation of Ordering Pos UKK Cadres at SMKN 3 Jambi City has been proposed to the Jambi City SMKN3 school and is expected to be implemented and carry out Health Effort activities through the Management of Occupational Health Effort Posts.